2021
DOI: 10.1016/s0140-6736(21)01379-9
|View full text |Cite
|
Sign up to set email alerts
|

Making miscarriage matter

Abstract: increasing burden in HIV among Black and Latinx Americans in southern USA was substantially driven by persistent social and structural determinants that must be addressed to improve health outcomes and the broader goal of human wellbeing and flourishing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This Cochrane review had already excluded a large study that had been retracted following concerns about the accuracy and trustworthiness of the trial data ( Ismail et al , 2018 ). We previously expressed concern on other three trials that were included in the 2019 Cochrane review ( Chong et al , 2021 ). Without these three studies, the treatment effect of progesterone becomes minimal and non-significant (RR 0.95, 95% CI 0.79–1.13).…”
Section: Discussionmentioning
confidence: 99%
“…This Cochrane review had already excluded a large study that had been retracted following concerns about the accuracy and trustworthiness of the trial data ( Ismail et al , 2018 ). We previously expressed concern on other three trials that were included in the 2019 Cochrane review ( Chong et al , 2021 ). Without these three studies, the treatment effect of progesterone becomes minimal and non-significant (RR 0.95, 95% CI 0.79–1.13).…”
Section: Discussionmentioning
confidence: 99%
“…Study indicated a significant association between each 10unit increase in SO2 and spontaneous miscarriage in lag 0 and 9 days. Chong et al [1] also opined that pregnant women should avoid polluted air. Desai did a study to know the impact of miscarriage under reporting on pregnancy data and related research.…”
Section: Discussionmentioning
confidence: 99%
“…Miscarriage, defined as the loss of a pregnancy before viability, occurring in more than 10% of women affecting woman's overall health, is one of the most prevalent negative reproductive outcomes around the world [1]. Knowing occurrence, causes and prevention of recurrence are great persisting challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, one of the analyzed trials within the review has since been retracted 51 . Further concerns have emerged over other studies incorporated in the analysis 52 . In response, Cochrane conducted another meta-analysis in 2021, including 7 randomized trials with a total cohort of 5682 women.…”
Section: Critical Studies On Progesterone Supplementationmentioning
confidence: 99%